“They recognize me as a doctor”: A peer mobilisation training programme to promote oral HIV self-testing and referral for acute HIV infection screening among gay and bisexual men and transgender women in coastal Kenya, an exploratory study - Shaun Palmer; Maartje Dijkstra; Alex Kigoro; Khamisi Mohamed; Nana Mukuria; Shally Mahmoud; Evanson Gichuru; Elise M. van der Elst; Eduard J. Sanders (PLoS ONE, 2025)
Background Targeted peer mobilisation can improve access to HIV testing and care and may impact onward HIV transmission. We describe a qualitative exploration of the experience with a peer mobilisation training programme for oral HIV self-testing (OST) and referral for acute HIV infection (AHI) testing among gay and bisexual men (GBMSM) and transgender women (TGW) in coastal Kenya. Methods The training programme covered five modules: 1) safe sex, 2) OST, 3) AHI, 4) HIV partner notification services, and 5) mobilisation skills. Mobilisers attended two training sessions and weekly meetings between March and June 2019. Mobilisers offered OST to GBMSM and TGW peers and extended an AHI referral card for point-of-care HIV-RNA testing when peers reported AHI symptoms. Two focus group discussions with 18 mobilisers and 15 in-depth interviews with mobilised clients who were newly HIV diagnosed were conducted to explore the experiences of the training programme. Results Mobilisers felt empowered through the training programme, which enhanced their mobilisation skills across two areas: (1) networking skills and (2) client empowerment. Facilitators for HIV testing were confidentiality of the OST, presence of STI symptoms, and building trust between mobilisers and clients. Mobilisers and clients reported challenges as: (1) misconceptions regarding OST and symptoms of AHI, (2) logistical and financial issues, and (3) stigma and security concerns. Discussion Our training programme facilitated peer mobilisers to extend OSTs among GBMSM and TGW in coastal Kenya while it was more difficult to refer clients directly for AHI testing. Mobilisers felt empowered through enhanced mobilisation skills which helped them to mobilise clients for HIV testing. A targeted training programme was helpful in mobilising peers to take up HIV testing.